Oral non-Hodgkin lymphomas: Studies of EBV and p53 expression - Iamaroon A. (2014)
OBJECTIVES: The aims of the study were to assess sociodemographic and clinicopathologic characteristics of patients with oral non-Hodgkin lymphomas (NHLs) and the expression of Epstein-Barr virus (EBV) and p53. MATERIALS AND METHODS: The clinical and pathologic features of 11 patients with oral NHLs were studied. The expression of EBV mRNA and p53 protein were studied by means of in situ hybridization and immunohistochemical methods in 11 formalin-fixed, paraffin-embedded specimens from these patients. RESULTS: The patients' age ranged from 13 to 70 years with the mean of 42 years. Human immuno-deficiency virus (HIV) status was documented in five of the 11 patients and three were known to be HIV-positive. The most common locations were gingiva and alveolar mucosa. Pain and tenderness were major symptoms of the patients. The most common histologic subtype was diffuse large-cell, intermediate-grade NHL. Eight of 11 cases (72.7%) showed positive expression of p53 protein. Four of 10 cases (40%) expressed EBV-encoded RNA (EBER) transcripts. All known HIV-positive cases were EBV-positive. CONCLUSIONS: The findings suggest that appropriately expressed p53 protein may play a role in tumorigenesis of oral NHLs. In addition, EBV may be involved with the pathogenesis of oral NHLs particularly in patients with HIV infection.